2020
DOI: 10.5539/jas.v12n9p173
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Perspective in the Selection of Bean Genotypes

Abstract: Changes in the relative performance of genotypes have made it necessary for more in-depth investigations to be carried out through reliable analyses of adaptability and stability. The present study was conducted to compare the efficiency of different informative priors in the Bayesian method of Eberhart & Russel with frequentist methods. Fifteen black-bean genotypes from the municipalities of Belém do São Francisco and Petrolina (PE, Brazil) were evaluated in 2011 and 2012 in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Similar results were observed byOliveira et al (2020), who observed the performance of complex interactionTable 3. Summary of the joint variance analyzes of the carioca bean competition trials, evaluated in the state of Pernambuco, from 2014 to 2015.…”
supporting
confidence: 88%
“…Similar results were observed byOliveira et al (2020), who observed the performance of complex interactionTable 3. Summary of the joint variance analyzes of the carioca bean competition trials, evaluated in the state of Pernambuco, from 2014 to 2015.…”
supporting
confidence: 88%